2015
DOI: 10.1016/j.tecto.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Late-Paleozoic emplacement and Meso-Cenozoic reactivation of the southern Kazakhstan granitoid basement

Abstract: International audienceThe Ili-Balkhash Basin in southeastern Kazakhstan is located at the junction of the actively deforming mountain ranges of western Junggar and the Tien Shan, and is therefore part of the southwestern Central Asian Orogenic Belt. The basement of the Ili-Balkhash area consists of an assemblage of mainly Precambrian microcontinental fragments, magmatic arcs and accretionary complexes. Eight magmatic basement samples (granitoids and tuffs) from the Ili-Balkhash area were dated with zircon U-Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 145 publications
(345 reference statements)
1
35
0
1
Order By: Relevance
“…These studies demonstrated that following the final closure of the Palaeo‐Asian (or Turkestan) Ocean and amalgamation of the terranes in the late Paleozoic, the Tian Shan experienced several major periods of cooling during the Mesozoic to Cenozoic. During the Mesozoic, distinct cooling events have been interpreted as related with exhumation in response to a number of Cimmerian collisions (e.g., the collisions of Qiangtang, Lhasa, and Karakorum with Eurasia; De Grave et al, ; Dumitru et al, ; De Pelsmaeker et al, ; Gillespie et al, ; Glorie & De Grave ; Jolivet et al, ; Käßner, Ratschbacher, Jonckheere, et al, ). The subsequent Cenozoic collision of India with Eurasia not only generated the Himalayas and the uplift of the Tibetan Plateau but is also thought to have driven uplift and deformation in the Asian continental interior, including the Tian Shan and other intracontinental mountain ranges (e.g., Bouilhol et al, ; Clift et al, ; Molnar & Tapponnier, ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that following the final closure of the Palaeo‐Asian (or Turkestan) Ocean and amalgamation of the terranes in the late Paleozoic, the Tian Shan experienced several major periods of cooling during the Mesozoic to Cenozoic. During the Mesozoic, distinct cooling events have been interpreted as related with exhumation in response to a number of Cimmerian collisions (e.g., the collisions of Qiangtang, Lhasa, and Karakorum with Eurasia; De Grave et al, ; Dumitru et al, ; De Pelsmaeker et al, ; Gillespie et al, ; Glorie & De Grave ; Jolivet et al, ; Käßner, Ratschbacher, Jonckheere, et al, ). The subsequent Cenozoic collision of India with Eurasia not only generated the Himalayas and the uplift of the Tibetan Plateau but is also thought to have driven uplift and deformation in the Asian continental interior, including the Tian Shan and other intracontinental mountain ranges (e.g., Bouilhol et al, ; Clift et al, ; Molnar & Tapponnier, ).…”
Section: Introductionmentioning
confidence: 99%
“…A Late Carboniferous unconformity is also archived in the North Balkhash (Chen, Seitmuratova, et al, ). Furthermore, the regional extension in a post‐orogenic regime was thought to give rise to the Late Carboniferous sinistral strike‐slip of the Darbut Fault (De Pelsmaeker et al, ; Lin, Sun, Xue, & Zhang, ) and coeval and subsequent post‐collisional plutons (e.g., Biske, ; Chen, Seitmuratova, et al, ; Gao et al, ; Han et al, ; Liu, Han, Chen, et al, ; this study) and continental volcanic rocks (Biske, ; Tan, Zhou, Yuan, Fan, & Yue, ; Zong et al, ) in both the North Balkhash and West Junggar areas. More importantly, a total of 232 detrital zircon U–Pb ages from modern river sands in the central WJT contain no record of Mesozoic and Cenozoic magmatic events (Liu et al, ).…”
Section: Discussionmentioning
confidence: 67%
“…The West Junggar terrane (WJT), located between the Irtysh–Zaysan suture zone and the North Tianshan suture zone (Figure b), is the most prominent and extensively studied segments of the CBJ arc–accretionary system (Xiao et al, ). It is now well understood that the WJT consists largely of Palaeozoic arcs and accretionary complexes, and mainly formed in response to the subduction of the Junggar – Balkhash oceanic crust (De Pelsmaeker et al, ; Han, Ji, Song, Chen, & Zhang, ; Liu et al, ; Liu, Han, Chen, et al, ; Liu, Han, Ren, et al, ). The subduction of the Junggar – Balkhash Ocean has been recently proposed to initiate in an intra‐oceanic setting by at least the Early Cambrian (Liu et al, ; Ren et al, ), whereas the following subduction and accretion processes and closure of this ocean remain debated, due to the complicated tectonic phases and latest Palaeozoic to Mesozoic reactivation of strike‐slip faults (Chen et al, ; Choulet et al, ; De Pelsmaeker et al, ).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations